2019
DOI: 10.1055/s-0039-1688905
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Alcohol and Low Birthweight: A Systematic Review and Meta-Analysis

Abstract: Objective To investigate the relationship between maternal exposure to alcohol and low birthweight (LBW). Methods The literature search was performed in January 2017 using the following electronic databases: Medline, Embase, LILACS, SciELO, Web of Science, Scopus, CINHAL, Proquest, and PsychInfo. The search strategy used the following terms: alcohol drinking, binge drinking, alcohol-related disorders, alcoholism, alcohol addiction/use/abuse/consumption, light/moderate/social/low drinking, low birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…Preventive strategies were divided into the 10 following categories: midwifery care, health promotion programs for smoking cessation, alcohol reduction during pregnancy, folic acid, vitamin D, iron, and zinc supplementation, a well-balanced diet, COVID-19 vaccination and cannabis use during pregnancy. The most significant and high-quality publications focusing on preventive strategies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventive strategies were divided into the 10 following categories: midwifery care, health promotion programs for smoking cessation, alcohol reduction during pregnancy, folic acid, vitamin D, iron, and zinc supplementation, a well-balanced diet, COVID-19 vaccination and cannabis use during pregnancy. The most significant and high-quality publications focusing on preventive strategies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In retrospective cohort studies Pereira et al found that an alcohol intake during pregnancy appears to be associated with a lower birth weight. However, in prospective cohort studies and case-control studies the association between maternal exposure to alcohol and birth weight was not observed [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…29 Penting untuk diingat bahwa data terkait variabel perilaku merokok dan konsumsi alkohol bersifat subjektif dan berkaitan dengan keterbukaan individu. 30…”
Section: Original Articleunclassified
“…En particular, Pérez et al (2018), comentan que, los factores del estilo de vida, como el consumo de tabaco y alcohol durante el embarazo, aumentan el riesgo de bajo peso al nacer, parto prematuro y mortalidad perinatal. Además, según Lindell et al (2018), los problemas de peso materno, la obesidad, la diabetes gestacional y la falta de suplementos de ácido fólico se asociaron con un mayor riesgo de preeclampsia, defectos neurológicos, cardíacos y orofaciales, alto peso al nacer y muerte fetal.…”
Section: Introductionunclassified